2019
DOI: 10.1186/s13018-019-1403-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy evaluation of three-dimensional printing assisted osteotomy guide plate in accurate osteotomy of adolescent cubitus varus deformity

Abstract: Background: This present study is aimed to retrospectively assess the efficacy of three-dimensional (3D) printing assisted osteotomy guide plate in accurate osteotomy of adolescent cubitus varus deformity. Material and methods: Twenty-five patients (15 males and 10 females) with the cubitus varus deformity from June 2014 to December 2017 were included in this study and were enrolled into the conventional group (n = 11) and 3D printing group (n = 14) according to the different surgical approaches. The operation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 26 publications
0
40
1
3
Order By: Relevance
“…Then, the closed-wedge osteotomy was performed by cutting through a slit on the template and using the reduction guide to align the bone [15]. Since then, many researchers have tried to develop an individualized navigation template for the lateral closed-wedge osteotomy for the CVD [9,16,17] and showed the advantages of this technique with respect to determining the osteotomy angle, osteotomy plane, and rotational angle. In this study, we innovatively designed the customized osteotomy guide to place on the posterior surface of the distal humerus due to the need for a posterior slit for the biplanar Chevron osteotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the closed-wedge osteotomy was performed by cutting through a slit on the template and using the reduction guide to align the bone [15]. Since then, many researchers have tried to develop an individualized navigation template for the lateral closed-wedge osteotomy for the CVD [9,16,17] and showed the advantages of this technique with respect to determining the osteotomy angle, osteotomy plane, and rotational angle. In this study, we innovatively designed the customized osteotomy guide to place on the posterior surface of the distal humerus due to the need for a posterior slit for the biplanar Chevron osteotomy.…”
Section: Discussionmentioning
confidence: 99%
“…It had been reported that preoperative 3D models can help surgeons plan operations, assist young doctors in learning surgical methods, and enhance communication between patients and surgeons ( Liu et al, 2020 ). Moreover, preoperative 3D printed models, surgical guide plates, and customized implants in orthopedic clinical application exhibited significant advantage, including the individual customization, rapid manufacturing, and efficient intraoperative drilling and osteotomy ( Zhang et al, 2019a , b ; Dong et al, 2020 ). In present study, assisted 3D printed model showed the focus of thoracic tuberculosis and the destruction of vertebral bodies directly, which could enhance the comprehension of spinal tuberculosis and the necessity of surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although 3D printing assisted guide plates have been diffusely applied in clinical correction researches of cubitus varus deformity, developmental dysplasia of the hip, spinal scoliosis, hallux valgus and other deformities [17][18][19][20], while the application in ATE malformation correction has been rarely reported. Previously, Windisch et al [21] applied 3D printing technology to fabricate a physical model of ATE malformation with a magnification of 4 times for surgeons to accurately analyze all bone and joint deformities, and perform preoperative planning, but this application only played the most basic role of 3D printing.…”
Section: Discussionmentioning
confidence: 99%